Association of serum bilirubin with longevity: Evidence from a retrospective longitudinal study and cross-sectional data - Chmielewski, Piotr; Strzelec, Bartłomiej; Chmielowiec, Jolanta; Chmielowiec, Krzysztof; Borysławski, Krzysztof (Anthropological Review, 2017)
Bilirubin is a potent antioxidant and an important anti-inflammatory factor. Therefore, there has been an increasing focus on serum bilirubin as a negative risk factor of cardiovascular mortality in men and an indicator of improved survival in both sexes, but the direct mechanisms of these links and the causes of sex differences are not well understood. Moreover, the evidence from longitudinal studies on effects of bilirubin on longevity is limited. In this study, we retrospectively analyzed two groups of older adults to explore age-dependent changes in serum bilirubin levels and their associations with long-term survival in both sexes. Longitudinal data from 142 individuals (68 men and 74 women) aged 45 to 70 years were compared with cross-sectional data from 225 individuals (113 men and 112 women). The latter group was divided into four categories of survival, i.e. 53, 63, 68, and 76+ based on data on lifespan. ANOVA, t-test, and regression analysis were run. The analysis of the longitudinal data showed an increase in serum total bilirubin levels in men (0.3038e0.093x, R2 = 0.667) and women (0.1838e0.0187x, R2 = 0.950), while the analysis of cross-sectional data revealed a U-shaped pattern of age-related changes in men (0.001x2 - 0.1263x + 4.4524, R2 = 0.999) but an inverted U-shaped pattern in women (0.0006x2 + 0.072x - 1.6924, R2 = 0.195). On balance, these results suggest that elevated but normal bilirubin levels might confer a survival advantage in older men but not women. Alternatively, the positive relationship between serum total bilirubin and lifespan was not causal but coincidental. Further studies are needed to elucidate the direct mechanisms of the association between serum bilirubin levels and longevity in elderly people of both sexes.